Jawabanmu

2014-03-04T22:34:48+07:00
A) a=6, b=4p+1, c=2p                                    b) x1 + x2 = 1
 x1 . x2 = 1                                                       -b/a = 1
c/a=1                                                               -(4p+1)/6 = 1
2p/6=1                                                                -4p-1=6
p=6/2=3                                                              -4p=7
                                                                             p=-7/4=-1,75